Representações sociais sobre os direitos dos animais : subsídios para a formulação de políticas públicas de proteção aos animais de companhia e de combate ao abandono de cães e gatos - Agostini, Sueli Aparecida (2014)
In this dissertation, the social representations on animal rights in contemporary Brazilian society were investigated. The purpose was to seek to understand why animals have not yet achieved the status of legal beings in Brazil, considering that cats and dogs have for a long time lived very closely with human beings. Yet, they are still treated as objects that can be disposed of at any moment, without any feelings of pity or regret. In addition, there is no punishment for those who violate the animals? rights to a life free from mistreatment and abandonment. The theory of social representations developed by sociologist Pierre Bourdieu was utilized in the development of this dissertation, since it claims that social representations are, on the one hand, the social genesis of schemes of perception, thought and action, which constitute what is named by him as habitus, and, on the other, the social structures, which are named by him as social fields. The purpose of this work is to present proposals for the formulation of public policies to protect household pets and to combat the abandonment of dogs and cats, since the excessive population of such animals in urban centers have forced public agencies to find solutions to this problem. In order to identify and present animal rights in Brazil, and in order to observe the measures adopted to fight the problem of the abandonment of dogs and cats, documental research was carried out at municipal, state and federal legislation, as well as in the bibliography produced by the defenders of such rights, and visitation to two Brazilian cities, São Carlos, in the State of São Paulo, and Florianópolis, in the State of Santa Catarina.